2019
DOI: 10.3892/or.2019.7413
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA FTH1P3 promotes the proliferation and metastasis of cervical cancer through microRNA‑145

Abstract: Emerging evidence has revealed that long noncoding RNAs (lncRNAs) play crucial roles in the development and progression of tumors. The present study aimed to examine the roles and illustrate the underlying mechanisms of lncRNA ferritin heavy chain 1 pseudogene 3 (FTH1P3) in cervical cancer. The expression of lncRNA FTH1P3 and microRNA-145 (miRNA-145 or miR-145) in human cervical cancer samples and cervical cancer cell lines was detected by qRT-PCR (reverse transcription-quantitative polymerase chain reaction).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The high levels of lncRNA Ferritin Heavy Chain 1 Pseudogene 3 (FTH1P3) in UM correlate with proliferation, cell cycle, and migration. It is dysregulated in other cancers such as lung, cervical, glioma, esophageal carcinoma, and breast cancer [106][107][108][109][110]. It is suggested that lncRNA FTH1P3 decreases miR-224-5p expression and enhances Fizzled 5 and Ras-related C3 botulinum toxin substrate 1 (Rac1) expression, promoting cell cycle progression and migration [70].…”
Section: Oncogenic Lncrnas In Uveal Melanomamentioning
confidence: 99%
“…The high levels of lncRNA Ferritin Heavy Chain 1 Pseudogene 3 (FTH1P3) in UM correlate with proliferation, cell cycle, and migration. It is dysregulated in other cancers such as lung, cervical, glioma, esophageal carcinoma, and breast cancer [106][107][108][109][110]. It is suggested that lncRNA FTH1P3 decreases miR-224-5p expression and enhances Fizzled 5 and Ras-related C3 botulinum toxin substrate 1 (Rac1) expression, promoting cell cycle progression and migration [70].…”
Section: Oncogenic Lncrnas In Uveal Melanomamentioning
confidence: 99%
“…FTH1P3 is a newly identified lncRNA in cancer cells, and its overexpression in cancer cell lines and tissues has been demonstrated by several studies. FTH1P3 can promote cell proliferation, migration, invasion, and tumor progression in uveal melanoma [ 194 ], oral squamous cell carcinoma [ 193 ], laryngeal squamous cell carcinoma [ 195 ], cervical cancer [ 196 ], and NSCLC. Zheng et al reported that the expression level of FTH1P3 was upregulated in uveal melanoma cell lines (C918, MUM-2B, OCM-1A, and MUM-2C) compared to that melanocyte cell line (D78).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lncRNA PTCSC3 was reported as a biomarker for the treatment and prognosis of gastric cancer (Zhang et al., 2020 ). LncRNA FTH1P3 was highly expressed in cervical cancer cells and it could facilitate cell proliferation via interacting with miR‑145 (Lv & Zhang, 2020 ). LncRNA MATN1‐AS1 was downregulated in GBM cells and could repress cell proliferation and invasion through regulating RELA (Han et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%